1996
DOI: 10.1002/hep.510230619
|View full text |Cite
|
Sign up to set email alerts
|

The caffeine breath test does not identify patients susceptible to tacrine hepatotoxicity

Abstract: position of the drug in vivo. (HEPATOLOGY 1996;23:1429-Therapy with tacrine, a promising new treatment for 1435.) Alzheimer's disease, must be discontinued in up to 15% of patients because of hepatocellular toxicity. Recent studies using human liver microsomes have suggested that a single liver enzyme, cytochrome P450 1A2 Tacrine (1,2,3,4-tetrahydro-9 acridinamine monohy-(CYP1A2), catalyzes the major route of metabolism and drochloride monohydrate; Cognex, Parke Davis Pharelimination of tacrine, and also catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…We reasoned that if CYP1A2 activity is rate limiting in tacrine clearance, the results of these caffeine tests might predict tacrine kinetics in patients. This hypothesis is supported by an incidental observation we made when investigating tacrine liver toxicity [12]. In 39 patients with Alzheimer's disease, we found that CYP1A2 activity, as measured using the [ 13 C‐3‐ N ‐methyl] caffeine breath test, did not identify the individuals most susceptible to tacrine induced liver injury.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…We reasoned that if CYP1A2 activity is rate limiting in tacrine clearance, the results of these caffeine tests might predict tacrine kinetics in patients. This hypothesis is supported by an incidental observation we made when investigating tacrine liver toxicity [12]. In 39 patients with Alzheimer's disease, we found that CYP1A2 activity, as measured using the [ 13 C‐3‐ N ‐methyl] caffeine breath test, did not identify the individuals most susceptible to tacrine induced liver injury.…”
Section: Introductionsupporting
confidence: 51%
“…A significant amount of data obtained in in vitro systems supports a central role for CYP1A2 in tacrine metabolism [8, 9, 35]. Since both caffeine and tacrine appear to be largely metabolized by CYP1A2 [7, 8], we believed that the ability to metabolize caffeine should predict the apparent oral clearance of tacrine in patients with AD [12]. In support of our hypothesis, statistically significant correlations between each of the three caffeine test results and the oral clearance of tacrine were demonstrated (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…While no correlation was found between the caffeine test and theophylline clearance [ 20], the caffeine test has been shown to correlate with clozapine clearance [ 2]. Likewise, the caffeine breath test has been shown to correlate with the logarithm of the steady‐state plasma tacrine concentration [ 28]. While the present study was in progress, Fontana et al [ 29] published a study on the utility of caffeine based probes of CYP1A2 activity in predicting the pharmacokinetics of tacrine in 19 patients with Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, caffeine metabolite levels have been measured in urine in an attempt to monitor CYP1A2 activity ( 67–70), but this method has only been applied to patients with liver disease ( 70). A method using radiolabelled caffeine, in which the level of labelled CO 2 in patients’ breath is measured, has been used for some time ( 71, 72)…”
Section: Cyp1amentioning
confidence: 99%
“…Detailed reviews of CYP3A have been published by Watkins ( 17) and Wilkinson ( 87). Many probe drugs metabolized by CYP3A, including nifedipine ( 88), erythromycin ( 89–91) and lidocaine ( 72, 92–99), have been reported, and there have been numerous reports of the use of erythromycin (breath test) and lidocaine as probe drugs in liver function tests. Huang et al .…”
Section: Cyp3amentioning
confidence: 99%